The Robinson Mall Impact on FV and DS in Zapa Street, Bandar Lampung City - Ida Bagus Ilham Malik; Ilyas Sadad (Bandar Lampung University (UBL), 2014)
Robinson Mall Development has led to distribution of commercial activities and services in the city of Bandar Lampung. During this time, trading activities and services focused in the downtown area, is in The Tanjung Karang Pusat (TKP). So, centralization of comercial activity in TKP, led of many vehicles heading downtown and that have an impact on traffic congestion in the area of city center.Centralization of economic activity, such as mall, supermarket, traditional and modern market, etc, has caused problem in traffic in the TKP. Problem solving such as widening of roads and arrangements of parking, is not able to resolve the issue. So, it needed others solution to decrease traffic problem in TKP, one of solution is spread of comercial activity (IB Ilham Malik, 2013). That is mean, if there is a new application of permit to build shopping center or mall or modern market, city government will be give the permit if location of project outside of TKP area. For example; at Kemiling area, Way Halim area, Rajabasa area, Teluk Betung area, etc.Spread of commercial activity in Bandar Lampung relevan with regulation (regional regulation or Perda) on Spatial Planning, that is Perda No. 04 Year of 2004 on Spatial Planning of Bandar Lampung, and updated by Perda No. 10 Year of 2011 on the same thing. So, in line with the regulation, in some of areas in Bandar Lampung have comercial center too, such as Robinson Mall in the Rajabasa area, Boemi Kedaton Mall in Kedaton Area, Giant Supermarket and Giant Mall in Kemiling area and Antasari area, etc. And that situation, encourage of area growth and in the future will be the comercial activity area.